British medicine in the Peruvian Andes: the travels of Archibald Smith M.D. (1820-1870) Medicina britânica nos Andes peruanos: as viagens do médico Archibald Smith (1820-1870) - Jorge Lossio (História, Ciências, Saúde: Manguinhos, 2006)
This article traces the travels of the Scottish physician Archibald Smith through the Peruvian Andes between the 1820s and 1860s. Despite his prominent role in the nineteenth-century Peruvian medical scene, almost nothing has been written on Archibald Smith. By exploring Smith's medical activities, publications, and debates, this article intends to uncover unexplored areas of Peruvian medical history, such as the animosity between local and foreign physicians during the post-Independence war era and the important role played by medical geography as a scientific discipline for redefining ethnical and regional issues. O presente artigo traça a vida e obra do médico escocês Archibald Smith durante sua permanência no Peru, entre as décadas de 1820 e 1860. Apesar de sua proeminente contribuição para a medicina peruana, quase nada foi escrito sobre Archibald Smith. Através da investigação das atividades, publicações e debates de que Smith participou, o artigo pretende desvendar áreas inexploradas da história da medicina no Peru, tais como a animosidade entre os médicos locais e estrangeiros no pós-guerra de independência e o papel importante da geografia médica como disciplina científica que redefine questões étnicas e regionais.